Interferon-γ Augments CD95(APO-1/Fas) and Pro-Caspase-8 Expression and Sensitizes Human Vascular Endothelial Cells to CD95-Mediated Apoptosis - Li, Jie Hui (American Society for Investigative Pathology, 2002)
We have examined the effects of interferon (IFN)-γ on expression and function of CD95 (APO-1/Fas) and associated proteins in cultured human umbilical vein and dermal microvascular endothelial cells (HUVEC and HDMEC, respectively). Unstimulated cells express only low levels of CD95; IFN-γ produces a time- and concentration-dependent increase of CD95 in both cell types at the mRNA and cell surface protein levels. IFN-γ also produces an increase in expression of pro-caspase-8 (FLICE/MACH) but does not significantly change expression of either Fas-associated death domain (FADD) protein or cellular FLICE inhibitory protein (cFLIP), other proteins associated with the CD95 death-inducing signaling complex (DISC). Neither resting nor IFN-γ-treated EC express detectable CD95L mRNA or protein. Untreated HUVEC and HDMEC show minimal apoptosis when transduced to express CD95L. Treatment of CD95L-transduced cells with IFN-γ causes apoptosis within 24 to 36 hours that can be blocked by antagonistic anti-CD95 antibody or by the caspase-inhibitory peptide zVAD-FMK. The extent of apoptosis is increased by co-treatment with either the protein synthesis inhibitor cycloheximide or the phosphatidylinositol 3-kinase inhibitor LY294002. Untransduced HUVEC treated with IFN-γ also undergo CD95-iniated apoptosis when mixed with CD95L-transduced HUVEC or when incubated with pharmacologically activated cytolytic T lymphocytes. Overexpression of CD95 in HUVEC confers sensitivity to CD95L in the absence of IFN-γ-treatment. We conclude that IFN-γ induces sensitivity of endothelium to CD95L-mediated apoptosis, and that this response may result from increased expression of CD95 and/or pro-caspase-8.